Aqueous dispersion of 1D van der Waals Mo6S3I6 crystal using biocompatible tri-block copolymer - Chae, Sudong; Oh, Seungbae; Choi, Kyung Hwan; Lee, Jin Woong; Jeon, Jiho; Liu, Zhixiang; Wang, Cong; Woo, Chaeheon; Shi, Liyi; Kang, Joohoon; Song, Si Young; Kim, Sung Jae; et al. (Ceramics International, 2021)
To achieve the stable dispersion of 1D van der Waals crystal Mo6S3I6 in aqueous media, the tri-block copolymer (Poloxamer) is used as dispersant. The head group of Poloxamer, hydrophobic polypropylene oxide parts can be adsorbed to Mo6S3I6 surface by hydrophobic interaction and the tail group with hydrophilic polyethylene oxide exposed to the outside of the Mo6S3I6 is soluble in water and can form sufficient steric hindrance, resulting in stable aqueous dispersion in nm scale. The excellent biocompatibility of aqueous dispersed nm scale 1D Mo6S3I6 was demonstrated by effective proliferation of C2C12 cells.
Keywords: Aqueous dispersions; Aqueous media; Dispersants; Hydrophobic interactions; Stable aqueous dispersions; Stable dispersions; Steric hindrances; Van der waals; 1D van der waals materials Mo6S3I6; Aqueous dispersion; Biocompatible material; Poloxamer